Strategy to Increase Knowledge and Awareness of Spring Management in Drawati Village through the SMAJA Program - Muhamad Zidan Rahmat; Andani Jamilah Mardotilah; Irgi Fadilah Rahman; Rifaldi Cahyanto; Shafa Isnanda Zoelianafasa; Lindawati Kartika (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The Campaka spring is one of the water sources used by the community in Drawati for consumption and agriculture. Since 2018, it has several problems: garbage which hinders irrigation and water quality decreases, the lack of awareness and knowledge of the local community and managers. Based on this background, the SMAJA program was initiated and implemented with the objectives of (1) increasing public awareness and knowledge through imah cai pancarama adopted from the house model; (2) Strategies and recommendations to sustainability of the SMAJA program. The method used is the kaizen method which consists of seiri, seiton, seiso, seiketsu and shitsuke. The collaboration of three techniques, namely counseling, training and mentoring. The number of target involved was 12 people but some activities could be attended by more than 40 people. The results are an increase in test scores of knowledge and concern. The value of knowledge from the original 2.00 to 3.70 on a scale of 1-5 and the value of concern for interests from 4.58 to 4.90 which was also measured from action from 2.50 to 3.80. The sustainability is formed in a quadruple helix.